Validitas Media Interaktif Wordwall Menggunakan Model Problem Based Learning Pada Pembelajaran Pendidikan Pancasila di Sekolah Dasar - Ainila Pradi Sespen; Reinita Reinita (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research is motivated by the use of technology-based media which is still rarely used, the media used by teachers uses conventional media and abstract media. Teachers focus on textbooks and picture media so that learning is less fun and less interesting. The aim of this research is to develop interactive wordwall media for learning Pancasila Education elements of the Unitary State of the Republic of Indonesia using a valid Problem Based Learning (PBL) model in class IV Elementary Schools in Cluster 1 West Padang District. The type of research carried out is Research and Development (R&D) with a 4-D development model, Phase I, namely Define, Phase II Design. Stage III Develop, stage IV namely Disseminate. The media that has been designed is then validated by the validator using a validation sheet in the form of a questionnaire. This product validation consists of material, language and media experts. The results of research on the development of wordwall interactive media which has a valid level of validity, material validity 95% (valid), language validity 95% (valid), media validity 87.5% (valid). It can be concluded that the use of "Wordwall Interactive Media for Bhinneka Tunggal Ika Elements Using the Problem-Based Learning Model in Class IV in Cluster 1 West Padang District" is valid for use in the learning process.